The leavers [book club bag] : a novel - Ko, Lisa (Algonquin Books of Chapel Hill, 2017)
"One morning, Deming Guo's mother, an undocumented Chinese immigrant named Polly, goes to her job at the nail salon and never comes home. With his mother gone, eleven-year-old Deming is left with no one to care for him. He is eventually adopted by two white college professors who move him from the Bronx to a small town upstate. Set in New York and China, the Leavers is the story of how one boy comes into his own when everything he's loved has been taken away--and how a mother learns to live with the mistakes of her past"--